Local Service Delivery in Nepal - World Bank (Washington, DC, 2014)
The effectiveness of public service delivery depends in large part on the capability, resources and inputs, and the motivation of frontline service providers at the local level. In Nepal a combination of de-concentrated line agencies and local bodies at the district, municipal, and village level provides inputs which are translated into delivery of service outputs and outcomes. Yet the relationships between line agencies and local bodies in service delivery are not well understood. The purpose of this report is to examine in detail the current dynamics of frontline service delivery to identify institutional limitations and present approaches to addressing them. This study seeks to map out the dynamics of service delivery at the local level through analysis of the institutional framework and actual practices in service delivery in 14 jurisdictions in the two districts of Dhankuta and Dhanusa. The study includes a detailed review of the provision of local roads networks and primary and lower secondary education. In this context, the report is divided into four parts: part one gives introduction; part two presents institutional framework for local service delivery; part three focuses on sub-national service delivery: local roads and primary education; and part four presents conclusions and recommendations to improve frontline service delivery.